Progesterone alters the bovine uterine fluid lipidome during the period of elongation. Issue 4 (April 2018) - Simintiras, Constantine A; Sánchez, José M; McDonald, Michael; Lonergan, Pat
Abstract : Successful bovine pregnancy establishment hinges on conceptus elongation, a key reproductive phenomenon coinciding with the period during which most pregnancies fail. Elongation is yet to be recapitulated in vitro, whereas in vivo it is directly driven by uterine secretions and indirectly influenced by prior circulating progesterone levels. To better understand the microenvironment evolved to facilitate this fundamental developmental event, uterine fluid was recovered on Days 12–14 of the oestrous cycle – the window of conceptus elongation initiation – from cycling heifers supplemented, or not, with progesterone. Subsequent lipidomic profiling of uterine luminal fluid by advanced high-throughput metabolomics revealed the consistent presence of 75 metabolites, of which 47% were intricately linked to membrane biogenesis, and with seven displaying a day by progesterone interaction ( P  ≤ 0.05). Four metabolic pathways were correspondingly enriched according to day and P4 – i.e. comprised metabolites whose concentrations differed between groups (normal vs high P4) at different times (Days 12 vs 13 vs 14). These were inositol, phospholipid, glycerolipid and primary bile acid metabolism. Moreover, P4 elevated total uterine luminal fluid lipid content on Day 14 ( P  < 0.0001) relative to all other comparisons. The data combined suggest that maternal lipid supply during the elongation-initiation window is primarily geared towards conceptus membrane biogenesis. In summary, progesterone supplementation alters the lipidomic profile of bovine uterine fluid during the period of conceptus elongation initiation.